Acute abdomen during pregnancy in Baghdad - Hizam*, Ahmed R.; Hamad*, Salam Othman; AL-Obaidi*, Safa M. (AL-Kindy College Medical Journal, 2012)
BackgroundThe diagnosis and important aspects in treating acute abdomen during pregnancy tend to be delayed due to the peculiar physiological features of pregnancy and the restrictions imposed on imaging diagnostic techniques such as x-ray and CT.Aim of the studyTo identify the most common causes of acute abdomen during pregnancy and identifying the approaches for early diagnosis and to take a correct decision for surgery and assigning the complications that may occur during and/or after surgery for the mother and the fetus.Patients and Methods This is a prospective study that involves data obtained from 91 pregnant patients admitted in the surgical wards in Baghdad teaching hospital during the period from January 2008 to December 2009 .All mandated surgical intervention.ResultsTotal surgical admission in Baghdad Teaching Hospital in 2008-2009 was 13485, total number of cases operated onas acute abdomen was 3374 and the total cases of acute abdomen operated on during pregnancy were 91 cases. The most common cause of acute abdomen during pregnancy is acute appendicitis which represents 70.3%.The most common age group of acute abdomen during pregnancy is between 25-29 years .The most common gestational age is the second trimester.The most common complaint of acute abdomen during pregnancy is right lower abdominal pain.The fetal condition was normal in 91.7% of total cases operated.ConclusionAcute abdomen during pregnancy represents a small proportion of the total cases of acute abdomen.It mostly presents during the second trimester and mostly caused by acute appendicitis. With proper management, the maternal and fetal outcome is good.Key words: Acute abdomen; Pregnancy; Baghdad Teaching Hospital.